Microstructure Characteristics of Chicken Feather Panels As An Alternative Wall Material - Ansarullah Faharuddin; Mukhthar Thahir syarkawi; Juhana Said; Muhammad Zainal Altim; Zulkarnain Hamson; Siti Aisah (Jurnal Penelitian Pendidikan IPA, 2023)
Chicken feather waste, after being finely chopped, is converted into feather panels which can be an alternative material in architecture. Chicken slaughter waste produces 4-9% of live weight in the form of feathers, requiring technology to make it a renewable alternative material. This research aims to process chicken feather waste into alternative materials for room dividers and building walls, reducing environmental impacts. Scanning is carried out to analyze the surface characteristics of the panels before they are applied as environmentally friendly materials. Previous research recorded a chicken feather panel density of 0.38-0.4, categorizing it as a soft stiff fiberboard material. Experimental engineering methods and material scanning in the microstructure laboratory using SEM reveal surface topography and material composition. The test results show that chicken feather panels can be recommended as a new alternative material in architecture. This discovery has the potential to use chicken feather waste in a sustainable manner, providing an environmentally friendly alternative and reducing the burden on the environment. The integration of these materials can enrich innovation in sustainable construction.